Momentos e número de aplicações de fungicidas e seu efeito sobre a duração da área foliar sadia e o rendimento de grãos em soja - Alessio, Diego (2008)
Studies carried out to evaluate chemical control of soybean diseases usually consider the diseased or removed but not the remaining leaf area. However, grain yield has shown to be more related to the health leaf area duration (DAFS) during the reproductive stages of soybeans. Programs of fungicidal sprays that allow for higher DAFS are expected to provide increased grain yields. With this hypothesis field trials were conducted at the FAMV/UPF in the summer season of 2006/07 using three soybeans cultivars of short, medium, and long crop cycles, and fungicidal spray programs with one application at R1, R3, or R5.1 and two applications at R1 and R5.1. The following fungicides were used: epoxiconazol 25 g a.i../ha-1 + pyraclostrobin 66.5 g a.i./ha-1, cyproconazol 24 g a.i./ha-1 + azoxystrobin 60 g a.i./ha-1 + 0.5% of the adjuvant Nimbus, and cyproconazol 24 g a.i./ha-1 + tryfloxistrobin 56.25 g a.i./ha-1 + 0.5% of the adjuvant Attach. Assessments of disease severity and leaf area were carried out collecting five plants per plot at the plant stages R1, R5.1, and R6. Later the area under the disease progress curves, the leaf area duration (DAF), the healthy leaf area duration (DAFS), and the grain yield were determined. The summer temperatures and rain amount in 2006/07 favored soybean rust, which occurred from 95 days after plant emergence for all cultivars. Therefore the long cycle cultivar was the most affected by rust. One application of fungicide, no matter the plant stage or the active ingredient, was not enough to maintain the leaf area along the reproductive period for three cultivars. Overall, two applications resulted in DAFS 15 to 26% superior to the other treatments, with increases in grain yield of 25 to 42%